The study of a defect evolution in iron under fatigue loading in gigacyclic fatigue regime (Fracture and Structural Integrity, 2015)
The work is devoted to the study of the damage accumulation in iron under gigacyclic fatigue (VHCF) regime. The study of the mechanical properties of the samples with different state of life time existing was carried out on the base of the acoustic resonance method. The damage accumulation (porosity of the samples) was studied by the hydrostatic weighing method. The obtained results show the accumulation of porosity in the volume of the sample during fatigue loading and corresponding decrease of the elastic properties. A statistical model of damage accumulation was proposed in order to describe the damage accumulation process. The model describes the influence of the sample surface on the location of fatigue crack initiation
Keywords: Gigacycle fatigue; Damage accumulation; Fatigue crack initiation